First Evaluation Switching From Ropivacaine to Highly Concentrated Bupivacaine in Intrathecal Mixtures for Cancer Pain. Issue 7 (28th June 2021) - Bienfait, Florent; Jubier‐Hamon, Sabrina; Seegers, Valérie; Pluchon, Yves‐Marie; Lebrec, Nathalie; Jaoul, Virginie; Boré, François; Delorme, Thierry; Robert, Julien; Bellanger, Martine; Sorrieul, Jérémy; Dupoiron, Denis
Abstract: Background: Intrathecal drug delivery is widely used for intractable cancer pain treatment. A combination of drugs with morphine and bupivacaine is recommended in first line therapy. In France, we use ropivacaine 10 mg/mL instead of bupivacaine 5 mg/mL, the only concentration available. Bupivacaine 40 mg/mL has been available in France only since July 2020 under temporary authorization of use. Objectives: The main objective of the study was to evaluate the safety, efficacy by pain assessment, to analyze drug dosage changes, to report adverse events (AEs) and conversion ratios switching from ropivacaine to bupivacaine. Secondary objective was to evaluate costs differences. Materials and Methods: We conducted this retrospective follow‐up monocentric study within the Institut de Cancérologie de l'Ouest (ICO) Pain Department in Angers, France. We included 14 patients aged 18 years and above, implanted with an Intrathecal Drug Delivery Systems (IDDS) for cancer pain treatment and followed up at ICO from July 2020 to February 2021 after switching from ropivacaine to bupivacaine. We used a continuous infusion mode and Bolus could be added through Personal Therapy Manager (PTM). Results: The median conversion ratio between ropivacaine and bupivacaine was 0.68 (0.65; 0.69) and resulted in no significant change in numeric rating scale evaluation ( p  = 0.10). We observed moderate and rapidly reversible AEs such as clinical hypotension (29%) and motor block after bolus (21%). The estimated median hospital cost per day was significantly lower ( p  = 0.05) for the bupivacaine refills than for the last ropivacaine pump refill, decreasing from US$ 61.7 (49.6; 70.5) to US$ 50.4 (45.9; 60.4). The median reimbursement per day from the National Health Insurance (NHI) was three times lower for bupivacaine pump refill when compared to the last ropivacaine pump refill ( p  < 0.01), decreasing from US$ 179.10 (156.79; 182.91) to US$ 64.59 (59.85; 71.89). Conclusion: Switching from ropivacaine to bupivacaine in IDDS appears more efficacious while remaining just as secure, and at lower cost.